Absolute photoluminescence quantum yields of IR26 and IR-emissive Cd1−xHgxTe and PbS quantum dots – method- and material-inherent challenges. Issue 1 (12th November 2014) - Hatami, Soheil; Würth, Christian; Kaiser, Martin; Leubner, Susanne; Gabriel, Stefanie; Bahrig, Lydia; Lesnyak, Vladimir; Pauli, Jutta; Gaponik, Nikolai; Eychmüller, Alexander; Resch-Genger, Ute
Abstract : Challenging photoluminescence quantum yield measurements in the spectral region of 800–1600 nm. Abstract : Bright emitters with photoluminescence in the spectral region of 800–1600 nm are increasingly important as optical reporters for molecular imaging, sensing, and telecommunication and as active components in electrooptical and photovoltaic devices. Their rational design is directly linked to suitable methods for the characterization of their signal-relevant properties, especially their photoluminescence quantum yield ( Φ f ). Aiming at the development of bright semiconductor nanocrystals with emission >1000 nm, we designed a new NIR/IR integrating sphere setup for the wavelength region of 600–1600 nm. We assessed the performance of this setup by acquiring the corrected emission spectra and Φ f of the organic dyes Itrybe, IR140, and IR26 and several infrared (IR)-emissive Cd1− x Hg x Te and PbS semiconductor nanocrystals and comparing them to data obtained with two independently calibrated fluorescence instruments absolutely or relative to previously evaluated reference dyes. Our results highlight special challenges of photoluminescence studies in the IR ranging from solvent absorption to the lack of spectral and intensity standards together with quantum dot-specific challenges like photobrightening and photodarkening and the size-dependent air stability and photostability of differently sized oleate-capped PbS colloids. These effects can be representative of lead chalcogenides. Moreover, we redetermined the Φ f of IR26, the most frequently used IR reference dye, to 1.1 × 10 −3 in 1, 2-dichloroethane DCE with a thorough sample reabsorption and solvent absorption correction. Our results indicate the need for a critical reevaluation of Φ f values of IR-emissive nanomaterials and offer guidelines for improved Φ f measurements.